ORGANISATIONAL READINESS OF BUILDING INFORMATION MODELLING IMPLEMENTATION: ARCHITECTURAL PRACTICES (Jurnal Teknologi (Sciences & Engineering), 2016)
Building Information Modelling (BIM) has been emerged to streamline the construction process by addressing interdisciplinary inefficiencies that have been rooted in the industry over the decades. However,Malaysiaconstruction industry is having barriers and difficulties in BIM adoption as there is no clear guidance and best practices in BIM implementation that can be learnt by them. The purpose of this research is to increase the awareness of BIM implementation towards enhancing the efficiency and productivity of architecture firms. BIM implementation requirements which cover management, process, people and technology were investigated through a total of 285 structured questionnaire surveys that distributed to professional or/and graduate architects at management and operational level. The overall severity of BIM implementation requirements were then established and ranked in conjunction with their perceived levels of importance and frequency of occurrence. Results indicate that the current low BIM status denominated among architectural practices in Malaysian construction industry. Predominantly attributed to the interoperability of BIM, selection of BIM tools, employment of pilot project, risks management and development of guidelines and standards that categorised under the management and process.Â